Assessment of Quality Characteristics of Mango Ginger (Curcuma amada Roxb.) Germplasm - Chatterjee, R.; Chattopadhyay, P. K.; Hnamte, V.; Chongtham, T.; Datta Ray, S. K. (International Journal of Bio-resource and Stress Management, 2023)
Mango ginger (Curcuma amada Roxb.) is popular in southern and eastern India mainly due to its typical pleasant flavor. It has carminative, stomachic properties. The rhizome is used for treatment of inflammatory conditions. Its essential oil has antifungal properties. Mango ginger finds an extensive application in the preparation of sweet meat and pickles because of its exotic mango aroma. It is also used for preparing preserves, candies, salads, sauces, chutney, etc. Nine germplasm namely Pundibari Col-1, Pundibari Col-2, Daspur, Krishnanagar Col-1, Krishnanagar Col-2, Kesinga, Sargiguda, Brahmapur, Cochin were assessed for their qualitative characters (curcumin, oleoresin, crude protein, total sugar and starch). Maximum fresh rhizome yield ha-1 was found to be highest (57.45 t) with Krishnanagar Col-2. Quality estimation indicated maximum oleoresin (6.57%), curcumin (0.43%) and total sugar (5.24%) in Kesinga germplasm while higher starch concentration (45.46%) and maximum crude protein (7.85%) were recorded with Daspur and Pundibari Col-2, respectively. The mango ginger, a potential crop with huge medicinal properties is totally unexploited. Hence, for its proper utilization it is essential to encourage its cultivation in the areas where it can be suitably grown. A grower may therefore select germplasm for cultivation according to specific purpose.